Does a Short-Term Increase in Incentives Boost Performance? - Vera Angelova; Thomas Giebe; Radosveta Ivanova-Stenzel (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
If agents are exposed to continual competitive pressure, how does a short-term variation of the severity of the competition affect agentsṕerformance? In a real-effort laboratory experiment, we study a one-time increase in incentives in a sequence of equally incentivized contests. Our results suggest that a short-term increase in incentives induces a behavioral response but does not boost total performance.
Keywords: C91; D91; J22; J33; L02; M05; 330; contest; tournament; real-effort; experiment; contract theory; forward-looking